DESIGN OF ISLAMIC HISTORY DOCUMENTARY IN THE SULTANCY BANTEN - Hirfat, Mohammad Alma; Sumarlin, Rully; Fiandra, Yosa (eProceedings of Art & Design, 2023)
Indonesia  is  the  largest  muslim  country  in  the  world  with  a  muslim population  of  236.53 million  people  or  about  86.88%  of  the  population.  This  is inseparable from the long history of the entry of Islam in the territory of Indonesia which was once known as the Nusantara region. The spread of Islam pioneered by traders in the midst of Hindu-Buddhist influence was very successful. Then came the various sultanates patterned Islam which helped in the spread of Islam throughout the archipelago one of which is the Sultanate of Banten. With the influence of the ruler, Islam can have a strong influence in the Land of Banten. But unfortunately the history seems to be lost and forgotten because the interest of young people to study history  is  very  minimal.  Therefore,  the  author  is  interested  in  designing  a documentary entitled=History of Islam in the Sultanate of Banten".Keywords: documentary film, Sultanate of Banten, islamic histor